Implementing family strengthening policy: an assessment of NGO experiences in the Western Cape, South Africa - Katzef, Carly (Department of Political Studies, 2025)
Mutually reinforcing health, education, and social development outcomes are rooted in the quality of children's relationships with primary caregivers in the home environment; yet multiple, compounding stressors make parenting a difficult task. Government policies that aim to support families do so through committing to provide an ‘enabling environment' for caregivers to fulfil this central role. The South African Revised White Paper on Families represents one such commitment. A key lever of support is family strengthening, which includes the provision of parenting support programmes to enhance caregiver-child relationships, and contribute to family and community safety and wellbeing. These programmes are largely delivered by non-governmental organisations (NGOs). However, as they are mandated, funded, and to some extent, regulated, by national policy frameworks, NGOs face several challenges. This qualitative study investigated the implementation of parenting support programmes by documenting the experiences of frontline NGO providers. Conducted in the Western Cape, it employed a semi-structured survey of NGOs, supplemented by key informant interviews with provincial government officials overseeing family strengthening in the province. The literature on parenting programmes highlights four interlinked factors which shape implementation outcomes, namely, availability of human and financial resources; co ordinating multiple institutions to support interventions in this joined-up policy area; and adopting evidence-based coupled with monitoring and evaluation practices to enhance programme design. Findings were generally consistent with the key implementation drivers in the existing literature: that government and NGOs alike lack the human and financial resources to execute a coordinated response to the family strengthening mandate. This limitation is partly attributed to the White Paper's siloed approach to family services, as well as a preference for statutory cases (such as foster care placement, and child abuse and neglect) over preventative support, such as parenting programmes. Monitoring and evaluation efforts are also hindered by resource constraints, which is compounded by governments' narrow quantitative reporting indicators that struggle to measure programme impact. However, there is an apparent effort in the sector to balance insights from both academic research and organisations' practice generated learnings in an attempt to define ‘evidence' usefully and realistically. Overall, this study identified the most prominent factors influencing the implementation of family strengthening policies, with a focus on the White Paper on Families, and drew out implications for improving policy design. Addressing family strengthening is a significant, yet complex, policy area that this research shed further light on by adding the experiences in the Western Cape province of South Africa as an additional piece of evidence to the existing literature. Future research avenues could explore the perspectives of both facilitators as well as beneficiaries (parents/caregivers) to contribute to a more comprehensive understanding of this little-known policy area.